Rfc5, a small subunit of replication factor C complex, couples DNA replication and mitosis in budding yeast. - Sugimoto, K (1996)
The inhibition of DNA synthesis prevents mitotic entry through the action of the S phase checkpoint. In the yeast Saccharomyces cerevisiae, an essential protein kinase, Spk1/Mec2/Rad53/Sad1, controls the coupling of S phase to mitosis. In an attempt to identify genes that genetically interact with Spk1, we have isolated a temperature-sensitive mutation, rfc5-1, that can be suppressed by overexpression of SPK1. The RFC5 gene encodes a small subunit of replication factor C complex. At the restrictive temperature, rfc5-1 mutant cells entered mitosis with unevenly separated or fragmented chromosomes, resulting in loss of viability. Thus, the rfc5 mutation defective for DNA replication is also impaired in the S phase checkpoint. Overexpression of POL30, which encodes the proliferating cell nuclear antigen, suppressed the replication defect of the rfc5 mutant but not its checkpoint defect. Taken together, these results suggested that replication factor C has a direct role in sensing the state of DNA replication and transmitting the signal to the checkpoint machinery.